Breast Cancer Screening and the Role of Administration in Zentsuji City - Fujita, Miho; Morimoto, Tadaoki (Journal of Japan Association of Breast Cancer Screening, 1996)
We investigated the primary factors related to quality improvement of mass screening and its effectiveness by collecting data on the results of breast cancer mass screening in Zentsuji City over the past twelve years. The total number of screenees was 17, 035, with a recent rate of about 25% of the population. Of these, 1, 281 (7.5%) required further examination, 1, 277 (99.7%) actually received further examination, 21 (0.12%) were found to have breast cancer, and in 8 the cancers were detected as interval cancer. During this period, we set up a plan for offering quality screening to the residents. This involved 1) meticulous data management, 2) good use of volunteers, 3) continued use of individual records, 4) throughgoing individual guidance by public health nurses, 5) cooperation with medical care institutions providing the third screening, and 6) data feedback to the examining physicians. This system enabled us to 1) maintain a comparatively high number of screenees, 2) a higher rate of screenees receiving further examination, 3) a higher cancer detection rate for mass screening by breast physical examination, and 4) an improved rate of detection of early-stage cancer. Some of the problems encountered were as follows : 1) The number of screenings per physician per hour reached nearly 40, making the schedule too overcrowded to maintain screening accuracy ; 2) Card filing and daily workload were complicated due to the continued use of individual cards ; 3) Only one institution in the city provided the third examination ; 4) The rate of screenees over 60 years of age, with a higher cancer detection rate was low. We intend to address these problems in order to improve future efficiency.